TEXTBOOK ANALYSIS IN THE SERVICE OF CHEMISTRY TEACHING - Ahtineva, Aija; University of Turku, Faculty of Education, Department of Teacher Education, Finland (2005)
The authors of textbooks have their own visions of contents and teaching methods, which should lead toa high level of scientific thinking. However, the textbook alone does not guarantee good results because the personal and social relationships between the teacher and students have a major influence on teaching and learning. Therefore, the teacher’s study of the textbook before teaching facilitates the teaching process. This paper suggests one method of textbook analysis. In the analysis, one upper secondary level course of chemistry instruction involved the use of a learning strategy: classification of the central concepts and a classification of activities based on task difficulty. The study also attempted to find out the goodness of fit between the national curriculum and the textbook chemistry course. The national objectives concerned the content of knowledge, social significance, emphasis on experimental chemistry, and inspiring students for further study. The majority of the textbook tasks fall into higher order categories characterized by knowledge structures assuming application of knowledge or making inferences. Good textbook activities also have social significance, and a number of experimental tasks are included. The textbook quality is further enhanced by up-to-date content. All of the above qualities are related to high study motivation.